Influence of the ABCB1-rs1045642 gene polymorphism on blood drug concentration in voriconazole-treated patients with severe invasive fungal infection - Zhang, Qian; Gao, Xing; Lv, Dongmei (Frontiers in Pharmacology, 2025)
This study aimed to investigate the impact of the ABCB1-rs1045642 gene polymorphism on the blood drug concentrations of voriconazole in patients with severe invasive fungal infections. A total of 101 patients treated with voriconazole were enrolled in this study. Polymerase chain reaction and Sanger sequencing were used to detect the genotype of ABCB1-rs1045642, and enzyme amplified immunoassay was used to detect the plasma trough concentration of voriconazole. We analyzed the impacts of patient genotype and the minimum concentration of voriconazole as well as investigated the treatment efficacy and rates of adverse reactions in patients with different genotypes. All subjects received standard-dose voriconazole treatment for 1 week, and the mean plasma concentration was found to be 4.5 (3.10, 6.90) mg/L. Three genotypes of ABCB1-rs1045642 were found in the study cohort, namely, wild type (CC type), heterozygous mutant type (CT type), and homozygous mutant type (TT type). There were 18 TT, 48 CT, and 35 CC type cases. Patients with different genotype groups and varying plasma trough concentrations did not differ statistically significantly in terms of the treatment efficacy or incidence of adverse events. Voriconazole plasma concentrations differed significantly among patients of different genders and ABCB1-rs1045642 genotypes. By incorporating gender into the multiple regression model, the regression equations were obtained as C1 = 6.09–1.33×Gender (male = 0, female = 1)-0.47× X1 (X1: T/T = 1, non-T/T = 0) and C2 = 6.09–1.33×Gender (male = 0, female = 1)-0.94×X1 (X1: T/T = 1, non-T/T = 0). The ABCB1-rs1045642 genotype was not found to affect voriconazole plasma trough concentrations in patients with invasive fungal infections admitted to the intensive care unit.